Penerapan Manajemen Mutu Pelayanan di Unit Rekam Medis Rumah Sakit PKU Muhammadiyah Surakarta - Susanto, Anton; , Sri Sugiarsi, SKM, M.Kes (2016)
The presence of medical records on a hospital is very important as a source of information derived from medical records. hence the need for good quality management in penggelolaan medical record as the basis for planning and assessing the performance of the medical service units. Medical record management problems still occur in PKU Muhammadiyah Hospital Surakarta the placement of medical records clerk kompetesinya not in accordance with, then relation to the facilities and infrastructure, especially its use is still not maximal capacity filling shelves. Then Standard Operating Procedure (SOP) in the management of existing medical records, but there are some that are not in accordance with the SOP. The purpose of this research is to know how the application of quality management services at the medical records of PKU Muhammadiyah Surakarta. This is a qualitative study using a case study approach (Case Study). Key informants were selected by the researchers comprises two coordinators managing medical records and informants Triangulation consists of Unit Manager Medical Record medical records staff. and hospital management includes planning unit, a team of hospital regulation and PPSDM. Data collection using structured interview techniques. The results showed PKU Muhammadiyah Hospital has conducted the planning of the recruitment of medical records personnel, facilities and infrastructure, SOP is done properly. Monitoring of the initial planning has been on a regular basis ie daily, monthly and yearly. Identification of the problems that arise are discipline, loyalty, rigor, which exceeds the shelf filing and SOP that is not run by baik.Tindakan and solutions that have been done is getting the warning letter (SP), cutting incentives, increase shelf filing. SOP socialization periodically.